Deep proteomics and phosphoproteomics reveal novel biological pathways perturbed by morphine, morphine‐3‐glucuronide and morphine‐6‐glucuronide in human astrocytes. Issue 1 (20th September 2020) - Dozio, Vito; Daali, Youssef; Desmeules, Jules; Sanchez, Jean‐Charles
Abstract: Tolerance and hyperalgesia associated with chronic exposure to morphine are major limitations in the clinical management of chronic pain. At a cellular level, neuronal signaling can in part account for these undesired side effects, but unknown mechanisms mediated by central nervous system glial cells are likely also involved. Here we applied data‐independent acquisition mass spectrometry to perform a deep proteome and phosphoproteome analysis of how human astrocytes responds to opioid stimulation. We unveil time‐ and dose‐dependent effects induced by morphine and its major active metabolites morphine‐3‐glucuronide (M3G) and morphine‐6‐glucuronide that converging on activation of mitogen‐activated protein kinase and mammalian target of rapamycin signaling pathways. We also find that especially longer exposure to M3G leads to significant dysregulation of biological pathways linked to extracellular matrix organization, antigen presentation, cell adhesion, and glutamate homeostasis, which are crucial for neuron– and leukocyte–astrocyte interactions. Abstract : Morphine, morphine‐3‐glucuronide (M3G) and morphine‐6‐glucuronide (M6G) activate human astrocytes via mitogen‐activated protein kinase and mammalian target of rapamycin signaling pathways. Morphine but especially prolonged exposure to M3G perturbed cellular pathways in astrocytes, which among others, are important for their interaction with neurons and leukocytes.